1982
DOI: 10.1002/jhet.5570190401
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of arylacetylhydrazones of carbonyl compounds with lead tetraacetate

Abstract: Oxidation of the title compounds 8, 9 with lead tetraacetate at room temperature gives a variety of products depending on the substituents on the carbonyl carbon atom. Thus, on oxidation of the aldehyde derivatives 8 1,3,4‐oxadiazolo derivatives 10 are obtained in good yields. However in some cases formation of N‐acetyl‐N‐arylacetyl‐N′‐benzoylhydrazines 11 is also observed, whereas oxidation of the ketone hydrazones 9 gives in good yields the 2H,5H‐1,3,4‐oxadiazoles 15 or substituted monoacetoxy‐ 17 and diacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…10 Thus, we thought that the hydroxyl group could interact with the hydrazone moiety to lead to the formation of 1,2-benzisoxazole N-imines 11. However, we found that monoacylhydrazones of type 10 do not yield N-imines 11 or the corresponding 1,3,4-oxadiazolines that would be formed if the reaction proceeded according to the literature data [4][5][6][7] about the unsubstituted hydrazones (Scheme 1), but instead they undergo a rearrangement resulting in "replacement" of the phenolic hydroxyl with an acyl substituent to give 3 1,2-diacylbenzenes 12, in excellent yields 70-90%, Scheme 3. o-Diacylbenzenes have been of interest primarily as fluorescence reagents for both qualitative and quantitative high sensitivity analyses for amines and amino acids.…”
Section: Cyclisation Reactions Of O-unsubstituted Arylketone N-acylhymentioning
confidence: 96%
See 2 more Smart Citations
“…10 Thus, we thought that the hydroxyl group could interact with the hydrazone moiety to lead to the formation of 1,2-benzisoxazole N-imines 11. However, we found that monoacylhydrazones of type 10 do not yield N-imines 11 or the corresponding 1,3,4-oxadiazolines that would be formed if the reaction proceeded according to the literature data [4][5][6][7] about the unsubstituted hydrazones (Scheme 1), but instead they undergo a rearrangement resulting in "replacement" of the phenolic hydroxyl with an acyl substituent to give 3 1,2-diacylbenzenes 12, in excellent yields 70-90%, Scheme 3. o-Diacylbenzenes have been of interest primarily as fluorescence reagents for both qualitative and quantitative high sensitivity analyses for amines and amino acids.…”
Section: Cyclisation Reactions Of O-unsubstituted Arylketone N-acylhymentioning
confidence: 96%
“…It has been known [4][5][6][7] o-Hydroxyarylketones are very interesting molecules both because of their potential to serve as starting materials in organic synthesis as well as because of their applications. 9 The presence of a hydroxyl and a carbonyl group at ortho positions to each other at the benzene ring allows the formation of novel heterocycles as well as other non-heterocyclic aromatic compounds.…”
Section: Cyclisation Reactions Of O-unsubstituted Arylketone N-acylhymentioning
confidence: 99%
See 1 more Smart Citation